(untitled) (Polish Yearbook of International Law, 2017)
This article is intended to provide a legally sound explanation of why and how the contemporary International Humanitarian Law and International Human Rights Law legal frameworks oﬀer tools to address the uncertainty, lack of information, and the consequences thereof in relation to missing persons and victims of enforced disappearances in the context of armed conﬂicts which predated the adoption of such frameworks. To this end, three scenarios will be examined: the contemporary claims of the families of those who were killed in the Katyń massacre in 1940; the claims for information and justice of the families of thousands who were subjected to enforced disappearances during the Spanish Civil War between 1936 and 1939; and the identifcation eﬀorts concerning those reported missing while involved in military operations in the context of the 1944 Kaprolat/Hasselmann incident which took place during the Second World War. Te analysis of these scenarios is conducive to the development of more general reﬂections that would feed into the debate over the legal relevance of the distant past in light of today’s international legal framework